Behavioral Disorders among People with Learning Disabilities - Al-Rubah, Yara AbdelRahman (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to detect behavioral disorders Of The study used the descriptive analytical approach, and concluded the study with several results, the most important of which is that learning difficulties are a disorder in the basic mental and psychological processes that affect the ability to learn reading, writing, and arithmetic. Also, cause shortcomings in learning different subjects. As for behavioral disorders among people with learning disabilities, they are the clear and noticeable deviation in the individual's feelings and emotions about himself and his environment, where the individual acts in a way that harms himself and others. The study also found that learning difficulties are divided into developmental difficulties, which are Functional disorders in the nervous system, psychological processes, and academic learning difficulties, which are the disorders that occur in the learning process. The study also showed the characteristics that characterize students with learning difficulties compared to their ordinary peers in general education. The results of the study also showed the existence of a number of important theories in the interpretation of behavioral disorders, such as the behavioral theory Psychoanalytic theory, biophysiological theory and environmental theory. The study included several recommendations, the most important of which is the need to provide training programs and seminars for people with learning difficulties to qualify them on how to treat behavioral disorders, mitigate their severity, and acquire good behavioral habits that Strengthening the capabilities of parents to face the disorders that their children are exposed to, and holding training courses for teachers to develop their abilities to deal with students with learning difficulties who have behavioral disorders.
Keywords: students; behavioral disorders; learning difficulties; education